Gender Wage Gap, Wage-Productivity Decoupling, and the Rate of Profit - Ossa, Daniel (Review of Radical Political Economics, 2024)
The declining gender wage gap (GWG) and the wage-productivity decoupling (WPD) are two emerging phenomena for the United States since the 1980s. This article proposes an extension to the usual decomposition method of the profit rate to account for both the GWG and the WPD on aggregate income distribution. It then uses this framework to study the US manufacturing sector from 1960 to 2017. It suggests that gender wage inequality was a source of profitability, especially before 1986, but which was slowly petered out. Since 2001, increases in the profit share have mostly been due to the WPD. These results highlight the relevance of gender-based inequality in the more traditional analysis of the profit rate dynamics.JEL Classification: B51, E11, E25, J16
Keywords: Gender Wage Gap; Rate of Profit; Wage-Productivity Decoupling; Income Distribution